Neuropilin-1 enforces extracellular matrix signalling via ABL1 to promote angiogenesis. (18th September 2014) - Raimondi, Claudio
Abstract : Neuropilin-1 (NRP1), together with neuropilin-2, belongs to the neuropilin family. Neuropilins are transmembrane proteins essential for vascular and neural development and act as co-receptors for secreted signalling molecules of the class 3 semaphorin and vascular endothelial growth factor A (VEGF-A) families. NRP1 promotes VEGF-A signal in blood vascular endothelium and semaphorin signal in lymphatic endothelium, by forming complexes with its co-receptors. Mouse mutant studies established that NRP1 expression is essential during development because mice lacking NRP1 expression die embryonically and show severe neuronal and cardiovascular defects. Even though the contribution of NRP1 to vascular development has been mainly ascribed to its function as a VEGF-A receptor, recent evidence suggests that NRP1 contributes to angiogenesis through VEGF-independent mechanisms. In the present paper, we provide an overview of NRP1 functions in the vasculature and discuss current knowledge of NRP1-dependent signalling in the endothelium.